Intradural Extramedullary Ependymoma with Hemorrhage: A Case Report - Changwon Choi; Sun Joo Lee; Sung Hwa Paeng; Hwa Jin Cho (Journal of the Korean Society of Radiology, 2023)
In adults, spinal ependymomas are usually found in intramedullary locations. However, intradural extramedullary spinal ependymomas are rare. Additionally, spinal ependymomas usually show iso to hypointensity on T1-weighted images without hemorrhage. Herein, we present a rare case of a 43-year-old female with a pathologically confirmed intradural extramedullary ependymoma that showed hyperintensity on T1-weighted imaging accompanied by hemorrhage.